El centro comercial: una "burbuja de cristal" - Federico Medina Cano (Estudios sobre las Culturas Contemporáneas)
The shopping center is the new place for commerce in today´s cities. It is the new public space that emerges when the old downtown looses its economic, politic and cultural leadership (the lived and enjoyed city disappears for the citizens). But the shopping center is not a democratic place that would gather all the inhabitants of the city, it is a restricted space in which there are exclusions and processes of segregation. The shopping center is half public, half private and works as a pasteurized world, A place that reduces the city into a private word, which is protected from the outside noise and social contradictions. Its suspended in time and attracts visitors with promises of comfort. It is a fancy, false paradise and a place to buy comfort. This article analyzes the forms as well as the symbolism of its architecture. Also, it studies its aesthetics, stock presentation and display windows. The shopping center is a structure that makes walking and buying easier. The article also shows the different uses that this place allows the visitor.